Development of methods allowing correlation of Dothistroma and Dothistromin in planta : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University, Manawatu, New Zealand - Owen, Timothy J. (Massey University, 2010)
Dothistroma septosporum is a fungal pathogen of pines with a worldwide distribution. It is responsible for the disease red band needle blight, in which necrotic lesions appear on infected needles. The red colour of the disease is due to the presence of the mycotoxin dothistromin. This toxin is structurally related to the better characterised mycotoxins aflatoxin and sterigmatocystin. The function of these toxins is unknown, but dothistromin is hypothesised to act as a competition factor. While much work has been done on D. septosporum and dothistromin in broth culture, in planta work has been limited by the methods available. This work focused first on the development of a method for the reliable and high yield extraction of DNA from infected lesions, as previously used methods were found to be inadequate. It was found that the addition of an enzyme lysis step to the Qiagen DNeasy protocol and the replacement of its column purification with chloroform purification gave a greatly increased yield of DNA with an acceptable loss of purity. To allow quantification of dothistromin from the same lesion samples, previously used assay systems were optimised and compared in their accuracy and sensitivity. An HPLC-fluorescence method was found most effective, and was able to accurately quantify dothistromin at single lesion quantities. The developed methods were used to give a correlation between Dothistroma biomass and dothistromin in lesions at various stages of development. While this correlation was not found to be statistically significant, continuation of this work should allow valid conclusions to be drawn. To give insight into the evolution of dothistromin biosynthesis, the genomes of other dothideomycetes were examined for the presence of dothistromin biosynthesis gene homologs. While no homologs were conclusively identified, a number of genes were shown to have similarity to known toxin biosynthesis genes. In summary, while not all research hypotheses were able to be proven or disproven, this work sets a firm basis for future investigation in these areas using the methods developed, and strongly suggests the direction continued study should take.
Keywords: Dothistroma; Dothistromin; In planta; Red band needle blight; DNA extraction; HPLC-fluorescence method